National Development and Local Reform : Political Participation in Morocco, Tunisia, and Pakistan - Ashford, Douglas Elliott (Book collections on Project MUSE., 1967)
The book is one of the many studies published by Princeton on the Near East and conforms to the high standards of quality and style of other Princeton publications. It is well written and presents a clear understanding of the politics in Morocco, Tunisia, and Pakistan and their changing political patterns since their independence from French and British colonialism. The book, as others written by the same author on Morocco and Tunisia, is the outcome of his intense research and travel in these countries. The author, as a political scientist, is engaged in research at the micro level: the political problems at the local level in the developing countries and their impact on development. The study stimulates some interesting thoughts and provides new dimensions to the problem of general development. During the past few years the reader interested in the general development of emerging countries has been overwhelmed with a vast amount of reading material, which, in the reviewer's judgment, is more likely to con fuse a clear analysis of problems of development. The problem is so complex that it is hard to discern any common ground in the different approaches adopted by different authors. Political scientists, sociologists, and economists all exhibit their own professional bias in their approaches by the lack of recognition of some of the significant contributions in related areas. So the study of national development, in the reviewer's opinion, is becoming similar to a group of blind men setting out to find the truth about an elephant, each by touching one limb of the animal and making some generalizations. -- from http://www.jstor.org (August 26, 2011).